Separating Will from Grace: An Experiment on Conformity and Awareness in Cheating - Toke R. Fosgaard; Lars Gårn Hansen; Marco Piovesan (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
In this paper we investigate if people cheat more when they observe their peers cheating because they conform or because they become aware that cheating is something to actively consider. In our experiment subjects toss a coin in private and report the outcome (white or black). We reward only those who report white and leave them the possibility to cheat without being discovered. In our 2x2 experimental design, we manipulated subjects' report sheet to i) suggest (or not) that cheating is an option; ii) suggest that their peers were honest (or dishonest). We find that increasing awareness of cheating as an option significantly increases the probability that women cheat; whereas men – who are already aware that cheating is an option - are not affected. When we suggest that peers have cheated, men cheat significantly more, whereas women do not.
Keywords: D63; K42; D81; 330; cheating; norms; conformity; awareness; gender differences